Struktur Mikro Sintaksis Takarir Instagram Ridwan Kamil dan Ganjar Pranowo - Silvia Ratna Juwita; Dadang S. Anshori; Vismaia S. Damaianti; Yeti Mulyati; Oktian Fajar Nugroho; Nurul Febrianti; Imam Sutanto (Ranah: Jurnal Kajian Bahasa, 2024)
Instagram is one of the social media of choice for 1.39 billion active users, including regional leaders who use this platform to convey information through captions in their content. The captions of Ridwan Kamil and Ganjar Pranowo, as regional heads with millions of followers, were chosen by researchers to be analyzed using a qualitative approach and critical discourse analysis (AWK) developed by Teun A. Van Dijk. Data taken from the Instagram captions of the two regional heads during the Cianjur earthquake disaster period at the end of November 2022 and the 2023 New Year's Eve floods that occurred in Semarang. The aim of this research is to identify the syntactic microstructure of regional leaders' Instagram caption discourse, which includes: (1) coherence, (2) sentence structure, and (3) use of pronouns. The results of the research show that there are similarities and differences in the estimates of the two regional leaders on each microstructural element. In Ridwan Kamil, elements of causal and positive coherence, active and passive sentence forms, as well as the use of the pronouns "I" and "we" were found. Meanwhile, in Ganjar Pranowo, elements of causal and positive coherence, active sentence forms, and the use of the pronoun "we" were found. AbstrakInstagram menjadi salah satu media sosial pilihan bagi 1,39 miliar pengguna aktif, termasuk pemimpin daerah yang menggunakan platform ini untuk menyampaikan informasi melalui takarir dalam kontennya. Takarir dari Ridwan Kamil dan Ganjar Pranowo, sebagai kepala daerah dengan jutaan pengikut, dipilih oleh peneliti untuk dianalisis menggunakan pendekatan kualitatif dan analisis wacana kritis (AWK) yang dikembangkan oleh Teun A. Van Dijk. Data diambil dari takarir Instagram kedua kepala daerah tersebut selama periode bencana gempa Cianjur pada akhir November 2022 dan banjir malam pergantian tahun baru 2023 yang terjadi di Semarang. Tujuan penelitian ini adalah untuk mengidentifikasi struktur mikro sintaksis wacana takarir Instagram dari pemimpin daerah tersebut, yang mencakup: (1) koherensi, (2) susunan kalimat, dan (3) penggunaan kata ganti. Hasil penelitian menunjukkan adanya persamaan dan perbedaan dalam takarir kedua pemimpin daerah pada setiap elemen struktur mikro. Pada Ridwan Kamil, ditemukan elemen koherensi sebab-akibat dan positif, bentuk kalimat aktif dan pasif, serta penggunaan kata ganti "saya" dan "kita". Sementara pada Ganjar Pranowo, ditemukan elemen koherensi sebab-akibat dan positif, bentuk kalimat aktif, serta penggunaan kata ganti "kita".